(untitled) (Applied Biological Research, 2016)
The present study was carried out at Horticultural Farm, Division of Fruit Science, SKUAST, Shalimar, Srinagar (Kashmir) during 2012-13 to evaluate various walnut pollinizers in improving the productivity and nut quality. Pollen germination and its viability, pollen production rate, anther and pollen morphology of ‘SKAU-W-0020’ and ‘SKUA-W-0022’ and influence of pollination method i.e. open and cross on nut and kernel characteristics was studied. Highest pollen viability (91.4%) was observed in selection ‘SKAU-W-0020’. Maximum pollen germination (51.5%) was observed in ‘SKAU-W-0020’ on medium containing agar agar powder (1%) + sucrose (15%) + boric acid (100 ppm) + CaCl2 (1 mM). Pollen production varied significantly within genotypes with maximum (1,43,75000) in ‘SKAU-W-0020’ and minimum (1,20,60000) in ‘SKAU-W 0022’. Maximum anther length (2457 µm) and width (1228 µm) was in ‘SKAU-W-0020’; however, maximum pollen length (35 µm) and width (39.6 µm) was in ‘SKAU-W-0022’. Nut weight, diameter, length and kernel length, weight and kernel percentage in ‘SKAU-W-0025’ and ‘SKAU-W 0015’ increased through cross pollination, however in ‘SKAU-W-0024’ and ‘SKAU-W-0008’ reverse trend was observed.